The science communication in social media theory of change evaluation framework: a system of establishing goals and assessing efficacy for knowledge brokers, intermediaries and boundary spanners - Cavanah, Sarah B.; Kemink, Kaylan (Frontiers in Communication, 2025)
The dissemination of scientific knowledge to the public, policymakers, and practitioners is crucial, particularly in democratic societies. Brokers, intermediaries, and boundary spanners (BIBS) facilitate this transfer through relationship-building and capacity development. Social media, widely adopted globally, provides BIBS with an important platform for engagement. However, current metrics, such as reach, inadequately measure the impact of these efforts on behavior and societal change. A Science Communication in Social Media Theory of Change (SciSM ToC) framework is proposed to align social media goals with appropriate evaluation methods. By integrating theory-based evaluation and strategic communication approaches, this framework provides a systematic process for planning, implementing, and assessing social media campaigns by BIBS. The SciSM ToC delineates inputs, activities, outputs, and outcomes, culminating in societal-level impacts. It incorporates established behavioral change models, such as the COM-B model, to address capacity factors (capability, opportunity, motivation) and emphasizes engagement as a dynamic, multidimensional process. Metrics are proposed to evaluate cognitive, affective, and behavioral changes, integrating practical tools like platform analytics and surveys. The framework allows for iterative evaluation, ensuring alignment with long-term goals and adaptation to diverse audiences. While limitations include its generalizability and exclusion of specific message design guidance, the SciSM ToC provides a flexible, practical tool for BIBS to maximize their social media effectiveness.